Case report: Cerebral amyloid angiopathy-related inflammation in a patient with granulomatosis with polyangiitis - Seifert, Rebecca M.; Rauch, Michael; Klingebiel, Randolf; Boese, Lennart-Maximilian; Greeve, Isabell; Rudwaleit, Martin; Schäbitz, Wolf-Rüdiger (Frontiers in Neurology, 2023)
Background Cerebral amyloid angiopathy-related inflammation (CAA-ri) defines a subacute autoimmune encephalopathy, which is presumably caused by increased CSF concentrations of anti-Aβ autoantibodies. This autoinflammatory reaction is temporally and regionally associated with microglial activation, inflammation and radiological presence of vasogenic edema. Clinical characteristics include progressive demential development as well as headache and epileptic seizures. In the absence of histopathologic confirmation, the criteria defined by Auriel et al. allow diagnosis of probable resp. possible CAA-ri. CAA-ri shows responsiveness to immunosuppressive therapies and a possible coexistence with other autoinflammatory diseases. Methods We present a case report and literature review on the diagnosis of CAA-ri in a patient with known granulomatosis with polyangiitis (GPA). Results Initially, the presented patient showed neuropsychiatric abnormalities and latent arm paresis. Due to slight increase in CSF cell count, an initial antiviral therapy was started. MR tomography showed a pronounced frontotemporal edema as well as cerebral microhemorrhages, leading to the diagnosis of CAA-ri. Subsequent high-dose steroid treatment followed by six intravenous cyclophosphamide pulses resulted in decreased CSF cell count and regression of cerebral MRI findings. Conclusion The symptoms observed in the patient are consistent with previous case reports on CAA-ri. Due to previously known GPA, we considered a cerebral manifestation of this disease as a differential diagnosis. However, absence of pachymeningitis as well as granulomatous infiltrations on imaging made cerebral GPA less likely. An increased risk for Aβ-associated pathologies in systemic rheumatic diseases is discussed variously.